Transformasi Kurikulum PAI di Era Merdeka Belajar: Antara Tantangan dan Peluang: Penelitian - Muhamad Ansori (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The transformation of Islamic Religious Education (PAI) curriculum has become a strategic necessity in the Merdeka Belajar era to face the challenges of 21st-century education and Society 5.0. Traditional PAI curriculum, dominated by rote learning and normative approaches, is considered insufficient in developing students’ character, creativity, and critical thinking. This study aims to analyze the direction of PAI curriculum transformation, identify challenges and opportunities in implementing Merdeka Belajar, and provide strategic recommendations for developing an adaptive, contextual, and holistic curriculum. The method employed is a literature review of 20 recent scholarly articles (2021–2025), including journals, policy documents, and comparative studies of PAI curriculum models. The analysis was conducted thematically to evaluate the role of teachers, integration of technology, learning flexibility, and the strengthening of character and local wisdom in the implementation of the Merdeka Belajar curriculum. The results indicate that PAI curriculum transformation requires teachers to act as facilitators and motivators, integration of digital technology and 21st century skills is crucial, and implementation strategies must consider local contexts and student needs. A holistic PAI curriculum can develop students who are adaptive, creative, faithful, and ready to face social, cultural, and technological dynamics in the modern era.